Biochemical and molecular aspects of selected cancers - Pretlow, Thomas G.; Pretlow, Theresa P.
This two-volume work not only includes much of the newer molecular biology research but also important earlier research in this area essential for the comprehensive understanding of the biochemistry of neoplastic diseases. As such it will provide an invaluable source of information for the young investigator. Human cancers, not experimental models of cancer, are emphasized.